Scope of Practice: Shared Decision-Making For Patient-Centered Care (Bangladesh Journal of Medicine, 2024)
Shared decision-making (SDM) represents a collaborative model of healthcare decision-making, contrasting the traditional unidirectional approach where physicians solely determine medical choices. SDM engages patients in evaluating options based on individual goals and values. In various clinical scenarios, SDM proves indispensable, enhancing patient satisfaction, treatment adherence, and reducing the likelihood of blaming physicians for adverse outcomes. Illustrated by the BRAN questions in the UK, SDM serves as a tool to explore benefits, risks, alternatives, and the option of doing nothing. Notwithstanding its benefits, SDM encounters implementation challenges, including time constraints and varying patient priorities. Elderly patients may face cognitive barriers, exacerbated by limited clinical trials catering to diverse geriatric needs. Nevertheless, SDM offers significant advantages, fostering strong patient-physician relationships, aligning with patient-centered care principles, and yielding positive outcomes. Physicians must integrate SDM consciously into clinical practice, recognizing its potential to improve patient satisfaction, quality of life, and overall healthcare outcomes.Bangladesh J Medicine 2024; 35: 122-123